2020
DOI: 10.3390/ijms21010306
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Application in Vineyards (Vitis vinifera L. cv. Tinto Cão) Induces Accumulation of Anthocyanins and Other Phenolics in Berries, Mediated by Modifications in the Transcription of Secondary Metabolism Genes

Abstract: Despite the numerous beneficial properties and uses of chitosan in agriculture, the molecular mechanisms behind its elicitation potential are still unclear. This study aimed at understanding the effect of chitosan application in the levels of phenolic compounds of Vitis vinifera L. red grapes berry skin (cv. Tinto Cão) during veraison. Grapevines were treated with chitosan (0.01% in 0.01% acetic acid) while control grapevines were sprayed with 0.01% acetic acid. Results showed that several monomeric anthocyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 44 publications
7
38
0
Order By: Relevance
“…Phenolic compounds, which play very important functions during pathogen infection (by e.g., providing mechanical strength through cell wall lignification processes) and in preventing oxidative stress, were also demonstrated to increase following elicitation with chitosan 28 . In fact, total phenolic content, and anthocyanins in particular, have been found to accumulate with chitosan treatment in leaf tissues of lemon balm and basil, and in cell cultures of grape vines 29 31 . Chitosan application also enhances the accumulation of several enzymatic antioxidants, including catalase, decreasing malondialdehyde (MDA) levels in leaf tissues thus improving plant antioxidant status 30 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds, which play very important functions during pathogen infection (by e.g., providing mechanical strength through cell wall lignification processes) and in preventing oxidative stress, were also demonstrated to increase following elicitation with chitosan 28 . In fact, total phenolic content, and anthocyanins in particular, have been found to accumulate with chitosan treatment in leaf tissues of lemon balm and basil, and in cell cultures of grape vines 29 31 . Chitosan application also enhances the accumulation of several enzymatic antioxidants, including catalase, decreasing malondialdehyde (MDA) levels in leaf tissues thus improving plant antioxidant status 30 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the cv. Tinto Cão, Singh et al [ 57 ] found in chitosan treated leaves and berry skins an up-regulation of several target genes (i.e., PAL , UFGT , ABCC1 , CHS , F3H , ANR , GST , and MATE1 ) that encode key enzymes and transporters involved in secondary metabolic pathways.…”
Section: Grapevine Responses To Biostimulantsmentioning
confidence: 99%
“…The results showed that monomeric anthocyanins, catechin, rutin, and quercetin-3-O-galactoside significantly increased in berry skins after treatment with chitosan. In addition, in leaves and berry skins, chitosan treatment upregulated several target genes (i.e., PAL, UFGT, ABCC1, CHS, F3H, ANR, GST, and MATE1) that encode key enzymes and transporters involved in secondary metabolic pathways [200]. On Mouhtaro cv.…”
Section: Chitosanmentioning
confidence: 99%